2013
DOI: 10.1200/jco.2013.31.15_suppl.8006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial of erlotinib (E) versus docetaxel (D) as second- or third-line therapy in patients with advanced non-small cell lung cancer (NSCLC) who have wild-type or mutant epidermal growth factor receptor (EGFR): Docetaxel and Erlotinib Lung Cancer Trial (DELTA).

Abstract: 8006 Background: E and D are standard cares for previously treated patients with advanced NSCLC. Although E shows significant clinical benefits over best supportive care in the EGFR wild type tumors, it remains unknown whether E or D is more active against the disease. Methods: This is an open-label, multi-center phase III study, sponsored by the Japanese National Hospital Organization. Patients were randomized to E (150 mg, daily), or D (60 mg/m2, q3w) by the minimization method according to gender, performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…The OS reported among patients in the erlotinib arm (median OS, 11.7 months) in the current study was in keeping with that demonstrated in previous studies, which reported an OS of 5.3 months to 14.8 months for patients treated with TKIs. [7][8][9]11,16,[22][23][24][25] However, the interpretation of the OS results of the current study might be confounded by the imbalance of crossover. In the current study, 61% of the patients in whom second-line pemetrexed failed crossed over to erlotinib therapy, but only 23% of the patients in whom second-line erlotinib failed crossed over to pemetrexed therapy.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The OS reported among patients in the erlotinib arm (median OS, 11.7 months) in the current study was in keeping with that demonstrated in previous studies, which reported an OS of 5.3 months to 14.8 months for patients treated with TKIs. [7][8][9]11,16,[22][23][24][25] However, the interpretation of the OS results of the current study might be confounded by the imbalance of crossover. In the current study, 61% of the patients in whom second-line pemetrexed failed crossed over to erlotinib therapy, but only 23% of the patients in whom second-line erlotinib failed crossed over to pemetrexed therapy.…”
Section: Discussionmentioning
confidence: 81%
“…14 The results of the current study demonstrated that erlotinib had efficacy similar to that of chemotherapy. In view of the evidence of the superiority of chemotherapy for patients with EGFR wild-type NSCLC, [23][24][25] the current study results indicate that EGFR TKIs should still be considered as an effective option for patients with EGFR wild-type and EGFR FISH-positive lung adenocarcinoma. The PFS noted among patients in the erlotinib arm (median PFS, 4.1 months) in the current study was notably longer than those in previous, unselected, populationbased studies or studies targeting wild-type EGFR, which reported PFS of 1.5 months to 3.6 months for patients on the TKI arm.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations